Can weekend warriors and other leisure-time physical activity patterns reduce the atherogenic index of plasma (AIP)? A cross-sectional analysis based on NHANES 2007-2018 - Niu, Yueyue; Chen, Xingjuan; Feng, Ling (Frontiers in Endocrinology, 2025)
BackgroundWith the shift in modern lifestyles, the relationship between physical activity (PA) and health has emerged as a significant concern in global public health. A sedentary lifestyle poses a substantial threat to cardiovascular health, particularly through the development of atherosclerosis, the primary pathological basis of cardiovascular disease (CVD) and a condition influenced by various lifestyle factors. The atherogenic index of plasma (AIP), a critical indicator for predicting cardiovascular disease risk, assesses an individual’s risk of atherosclerosis by reflecting the ratio of high-density lipoprotein cholesterol (HDL-C) to triglycerides (TG). Despite the recognized importance of PA, the impact of various physical activity patterns on AIP remains unclear.MethodsThis study utilized the National Health and Nutrition Examination Survey (NHANES) database from the United States. PA was assessed via a questionnaire, and participants were categorized into four groups: inactive, insufficiently active, weekend warriors (WW), and regularly active (RA). The AIP was calculated via the ratio of HDL-C to TG, with covariates such as age, sex, race, and body mass index controlled. Multivariate regression analysis served as the primary analytical method.ResultsThis study included a total of 24,504 participants. After adjusting for all potential covariates, RA (β=-0.044, P<0.0001) was associated with a significant reduction in AIP compared with WWs (β=0.01, P=0.65). Additionally, subgroup analysis and interaction tests showed that the PA-AIP association varied slightly among individuals with different education levels (P for interaction = 0.07) and marital statuses (P for interaction = 0.09), although these differences were small and did not reach statistical significance. Furthermore, restricted cubic splines (RCS) analysis revealed a significant, nonlinear, and negative correlation between total weekly PA and AIP among inactive individuals (P<0.001, nonlinearity P<0.001). The study found that 510 minutes of total physical activity per week is a threshold, beyond which the rate of decrease in AIP tends to slow down.ConclusionRA is more effective in reducing AIP than WWs are. For inactive adults, engaging in more than 510 minutes of PA per week significantly reduces the AIP.